Μελέτη και μοντελοποίηση αλληλεπιδράσεων οδηγών με βάση τη θεωρία λεκτικών πράξεων, προς την κατεύθυνση εμπλουτισμού συστημάτων αυτοματοποίησης της οδήγησης - Πορτούλη, Ευαγγελία (Σχολή Μηχανολόγων Μηχανικών, 2015)
This thesis studied the drivers’ communicative interactions, which constitute a necessary component of the driving task. These interactions are based on successive elementary communicative acts. It is a common observation that when drivers predict that their vehicle may be found in the future in dangerous proximity to another vehicle, they tend to intentionally communicate in advance their motion intent to the other involved drivers, so that they may jointly plan and execute a safe future motion plan. At a theoretical level, the objective of this thesis was to study the interactive part of the driving task, shedding light on the phenomenon of communication of drivers’ intent and their agreement on a future common motion plan. At a practical level, the aim of the thesis was to develop a model of drivers’ communicative interactions, for integration, as a manoeuvring negotiations level, in Driving Support and Automation Systems (DSAS), so that their functionality is more in accordance to human expectations.